Hemoglobin-associated CALR in proximal tubule cells can be used as a biomarker for idiopathic membranous nephropathy - Pang, Shuting; Tan, Qiuyan; Xie, Boji; Feng, Bingmei; Zhou, Rongbin; Liu, Zige; Wei, Haiyuan; Huang, Yian; Jili, Mujia; Xie, Yuli; Li, Shanshan; Zhao, Binran; et al. (Frontiers in Medicine, 2025)
ObjectiveIdiopathic membranous nephropathy (IMN) is the leading cause of nephrotic syndrome in adults. Given the limited diagnostic options currently available, we performed RNA sequencing (RNA-seq) of urinary cells to identify potential urinary biomarkers for IMN and to investigate its underlying disease mechanisms.MethodsWe conducted RNA-seq analysis on cells isolated from both first-void and second-void morning urine samples. By integrating these data with single-cell RNA sequencing (scRNA-seq) data from IMN and healthy kidney tissues, we performed comprehensive analyses including: Inflammatory index assessment, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, Gene Ontology (GO) functional annotation, Gene Set Enrichment Analysis (GSEA) enrichment analysis, Protein-Protein Interaction (PPI) network construction. Candidate differentially expressed genes (DEGs) were further validated using urinary cell RNA-seq data. Key genes were ultimately identified through Weighted Gene Co-expression Network Analysis (WGCNA) and subsequently verified by immunohistochemical and Quantitative Real-Time PCR (qRT-PCR) experiments of tissue expression patterns.ResultsOur findings demonstrate that the CALR gene is significantly associated with IMN pathogenesis and progression. Functionally, CALR plays crucial roles in both immune response (particularly in antigen presentation) and physiological processes (notably in hemoglobin production).